Peran Kuliah Kerja Nyata sebagai Wujud Pengabdian kepada Masyarakat di Universitas Islam Internasional Darullughah Wadda’wah Pasuruan - Juharoh, Juharoh (Universitas Islam Internasional Darullughah Wadda'wah, 2024)
The Community Service Program (KKN) is an implementation of the Tri Dharma of Higher Education, encompassing community service, teaching, and research. This study was conducted at Darullughah Wadda’wah Islamic Boarding School in Pasuruan, during the post-Covid-19 pandemic, focusing on the flagship program